Exploring the neuroprotective role of miR-335 in experimental Parkinson's disease - Lúcio, Ana Cecília Moita do Rosário (2021)
Tese de mestrado, Ciências Biofarmacêuticas, 2021, Universidade de Lisboa, Faculdade de Farmácia